ANALYSIS OF THE ENLARGEMENT A GARING IN THE URBAN VILLAGE HALL GADANG THE KOTO TANGAH IN PADANG WEST SUMATERA A PROVINCE - Mimin Giomitra Cahaya; Hendrik '; Mohamamad Ramli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Business analysis of research on enlargement fish garing ( tor soro ) implemented in november 2014 in urban village hall in the koto tangah gadang the city of west sumatra province .This research aims to understand how big business investment in the enlargement of fish out on a garing , to know how large the total fish production the cost of enlargement and garing business to know how much income and business profits enlargement fish garing. Based on the results of research and the total investment in total cost of production and the amount of rp 967.220.000 out gross income of rp 1.755.000.000 can in that net income of rp 787.780.000 that in a canKey Word: fish Garing, business feasibility, investment